Well-seasoned talks: the newspaper column and the satirical mode in South African letters. (2nd January 2019) - Sandwith, Corinne
ABSTRACT: In this article, I examine the popular satirical column "R. Roamer Esq." written by R.R.R. Dhlomo which appeared in The Bantu World newspaper. The study seeks to reassemble the archive of African intellectual and political life by foregrounding a hidden history of print culture practices and traditions. I assert the historical importance of the newspaper column and the satirical gesture in South African letters and emphasise the significance of the modes of humour and irony as forms of political resistance. In directing attention to the rhetorical and performative aspects of South Africa's protest history, the article expands on the political role of the African press in the aftermaths of colonialism in articulating new modes of agency, resistance and critique. In particular, Dhlomo's satirical column is approached as a space of literary expression in which opposition to various aspects of 1930s South African society is articulated in elusive, indirect and coded ways. As such, I advocate a reading of South African literary history that goes beyond the published literary text, one which can accommodate the idiosyncratic form of the newspaper column. In this sense, the newspaper itself is re-imagined as an important site of linguistic and genre-based experimentation, invention and play.